The Power of Proactive Information - Gonzalez, Luis Armando; Hernandez, Adolfo; Alfaro, Teddy (Qualitative and Quantitative Methods in Libraries, 2021)
Parliamentary libraries are part of parliaments. They provide information products and services related to their main role, that is, to support parliamentary functions regarding the law-making process, government oversight, and constituency work. Citizens use part of these products and services when they are available. The Library of the National Congress of Chile delivers a great part of its information services to Congress members and their staff, in the form of Web Systems and research documents generated by its professionals in matters of legislative interest. One of the Library’s main objectives is to become a Library 4.0, consolidating as a modern and innovative organization based on solid technological pillars arising from Industry 4.0, and by developing modern technological tools for data and information processing and usage, with a deep sense of collaboration with parliamentary work. In this context, the way in which the Library delivers its products and services to the parliamentary community -and indirectly to citizens- also requires modernization to provide a proactive and permanently updated service. The paper’s question is how to determine the effectiveness in the usage of such information products and services. In accordance with the notion that consumption online is the most appropriate form to distribute parliamentary outputs and that all online content should be suitable for mobile devices, the answer to the aforementioned research question is a technological solution that brings information products and services closer to the parliamentary community. Through a mobile application installed in smartphones and other mobile devices, Congress members and their staff could have the Library’s main information products and services “in the palm of their hand”, achieving greater deliverance efficiency and avoiding explicit service requirements. Safeguarding access roles, the same mobile application would also deliver public information to citizens. In this way, and following the concepts of Library 4.0 [2], providing the Library with ubiquity in the Massive Data Library and Context-Aware dimensions. This paper presents key guidelines used by the Library’s IT team for the design, development, and implementation of the said mobile application, under a user-focused approach. The implementation of this prototype application, still in the trial phase, would allow the Library to identify the main services and products used by parliamentarians and staffers, and to acknowledge their interests, needs and fieldwork, hence promoting a better informed parliamentary community.